Answer:
Option B
Explanation:
We can see that, from the picture provided, the graphs intersect at points( 0, 4 ) and ( - 4, 4 ), respective to functions f( x ) and g( x ). These intersection points makes each function equivalent to one another, and hence -
Function f( x ) where x = - 4 / Function g( x ) where x = - 4,
![f( - 4 ) = 4,\\g( - 4 ) = 4\\----------\\f ( - 4 ) = g ( - 4 )](https://img.qammunity.org/2021/formulas/mathematics/high-school/arap9nt3o2qlpmlf6s5kydl9e1wbdi2evo.png)
Respectively function f( x ) where x = 0 / Function g( x ) where x = 0,
![f( 0 ) = 4,\\g( 0 ) = 4\\----------\\f ( 0 ) = g ( 0 )](https://img.qammunity.org/2021/formulas/mathematics/high-school/1ka5k9hhfudtm3n1atto68qp98fkkwl2ba.png)
Your solution should be option b, " f(-4) = g(-4) and f(0) = g(0) "